BIOECOLOGY OF MEDICINAL PLANTS OF BUKHARA REGION - Kenjaeva Nozima Jobirovna (Scholars Digest Publishing, 2023)
The article describes in detail the botanical description, geographical distribution, used parts, above-ground parts, chemical composition, and use of medicinal plants found in Bukhara region.